2003
DOI: 10.1002/sce.10079
|View full text |Cite
|
Sign up to set email alerts
|

Mediating mental models of metals: Acknowledging the priority of the learner's prior learning

Abstract: This paper describes the conceptualizations, or mental models, of the nature of the bonding and structure of metals of a group of U.K. college students. It is suggested that these mental models may be understood in terms of the students' prior learning about covalent and ionic bonding, and the prevalence of a common alternative conceptual framework for chemical bonding labeled "the octet framework." This study illustrates the prominence of prior learning in channeling the interpretation of subsequent teaching,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 58 publications
(76 reference statements)
1
51
1
14
Order By: Relevance
“…The similar misconceptions were revealed also in the research of Taber (2003), which indicated that students thought metals had a few covalent bonds and mainly ionic and weak van der Waals forces. As mentioned by De Posada (1997), students commonly had misunderstandings and misconceptions related to the constitution of electric current in metals.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The similar misconceptions were revealed also in the research of Taber (2003), which indicated that students thought metals had a few covalent bonds and mainly ionic and weak van der Waals forces. As mentioned by De Posada (1997), students commonly had misunderstandings and misconceptions related to the constitution of electric current in metals.…”
Section: Discussionmentioning
confidence: 56%
“…Students also explained that there was no bonding in pure metals or there was just a force and not a real chemical bond (Table 1). In her other study, Taber (2003) asked students to describe and explain the bonding in metals to examine their conceptualisations, mental models related to the nature of the bonding and structure of metals, and they found that students had some difficulties and insufficient models as in the previous study.…”
Section: Internal Structures Of Metalmentioning
confidence: 94%
See 1 more Smart Citation
“…Ausubel considered prior knowledge to be the most significant factor in planning teaching, and the constructivist perspective acknowledges how the learners' existing conceptual frameworks are the resources for "making sense" of new information (e.g., Driver, 1989;Fensham et al, 1994), such that prior learning can "take priority" over the teacher's message (Taber, 2003b). Teachers are advised that teaching should therefore be planned in the light of a conceptual analysis of the topic to be taught (Heron et al, 1977), to determine the necessary prerequisite knowledge, as well the optimum order of presentation of material, etc.…”
Section: Learning Impediments: a Perspective From Learning Theorymentioning
confidence: 99%
“…This large body of knowledge revealed students' alternative conceptions on the following major aspects of the matter concept: conservation (BouJaoude, 1991;Stavy, 1990;Watson, Prieto, & Dillon, 1995), composition and structure (Benson, Wittrock, & Baur, 1993;Coll & Treagust, 2003;Doran, 1972;Griffiths & Preston, 1992;Krnel, Glazer, & Watson, 2003;Krnel, Watson, & Glazar , 1998;Novick & Nussbaum, 1978, 1981Nussbaum, 1985;Peterson, Treagust, & Garnett, 1989;Stavy, 1991;Taber, 2003), physical properties and change (Haidar & Abraham, 1991;Krnel, Watson, & Glazar, 1998;Lee et al, 1993;Osborne & Cosgrove, 1983;Shepherd & Renner, 1982), and chemical properties and change (Boo & Watson, 2001;BouJaoude, 1991;Hesse & Anderson, 1992;Johnson, 2000Johnson, , 2002Nieswandt, 2001;Solomonidou & Stavridou, 2000;Stavridou & Solomonidou, 1989Voelker, 1975;Watson, Prieto, & Dillon, 1995). This large body of knowledge covers grade levels from elementary to university and diverse cultural backgrounds.…”
Section: Children's Alternative Conceptions Of Matter From Elementarymentioning
confidence: 99%